NABI BARU VERSUS NEGARA - Zuly Qodir (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
This paper elaborate phenomenon the new Prophet in Indonesia. The New prophet on community left (separated/heretic) by Majlis Ulama Indonesia (MUI) because community crowded and heretic in religious mainstream (Islam). Why this growth? The ommunities where heretic Abrahamic Religions, but in Abrahamic Tradidition late growth. What simultan within social ills, for examples state failure management plralism SARA in Indonesia, or conection within religious mission (Dakwah) or this contemporary phenomena. This paper introduce state failure on dakwah/mission in Islam, pluralism management, and disruction national politics and economic growth. In this paper all so, describle mass dectruvtive on sect (heretece) community by MUI. This paper can by religious sociological perspective, thus religion seen social reality, not religion dogma and state preposition. The New Prophet diametral position with state (new prophet vis a vis state).